2013
DOI: 10.1007/s00253-013-4975-x
|View full text |Cite
|
Sign up to set email alerts
|

Hollow fiber culture accelerates differentiation of Caco-2 cells

Abstract: Caco-2 cells usually require 21 days of culture for developing sufficient differentiation in traditional two-dimensional Transwell culture, deviating far away from the quick differentiation of enterocytes in vivo. The recently proposed three-dimensional cultures of Caco-2 cells, though imitating the villi/crypt-like microstructure of intestinal epithelium, showed no effect on accelerating the differentiation of Caco-2 cells. In this study, a novel culture of Caco-2 cells on hollow fiber bioreactor was applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…Unlike cellulose acetate, polysulfone, and polyacrylonitrile, polyethersulfone (PES) hollow fibers (inner diameter of 900 µm; thickness of 330 µm; inner surface covered with microwells with 5–10 µm diameter) allowed cells to symmetrically form confluent monolayer on the inner lumen surface and to accelerate the cellular differentiation within a short time period (6 days of culture instead of 13 days of standard culture). Moreover, hollow 3D fiber cultures enhanced the activities of intestinal transports, like P‐glycoprotein, suggesting that, when cultured on curvy surface similar to the topography of the small intestine, Caco‐2 cells might become rapidly differentiated and polarized, sustaining the enterocyte‐like structures morphologically and functionally …”
Section: Intestinementioning
confidence: 99%
See 1 more Smart Citation
“…Unlike cellulose acetate, polysulfone, and polyacrylonitrile, polyethersulfone (PES) hollow fibers (inner diameter of 900 µm; thickness of 330 µm; inner surface covered with microwells with 5–10 µm diameter) allowed cells to symmetrically form confluent monolayer on the inner lumen surface and to accelerate the cellular differentiation within a short time period (6 days of culture instead of 13 days of standard culture). Moreover, hollow 3D fiber cultures enhanced the activities of intestinal transports, like P‐glycoprotein, suggesting that, when cultured on curvy surface similar to the topography of the small intestine, Caco‐2 cells might become rapidly differentiated and polarized, sustaining the enterocyte‐like structures morphologically and functionally …”
Section: Intestinementioning
confidence: 99%
“…Moreover, hollow 3D fiber cultures enhanced the activities of intestinal transports, like P-glycoprotein, suggesting that, when cultured on curvy surface similar to the topography of the small intestine, Caco-2 cells might become rapidly differentiated and polarized, sustaining the enterocyte-like structures morphologically and functionally. 67 In vivo scaffold assessment An ideal intestinal replacement should not only contain the different cellular components in each layer (such as circular and longitudinal smooth muscle components with intramuscular interstitial cells) but also integrate with the existing muscular and neuronal layers to receive cues from the central nervous system to facilitate peristalsis, gut motility, digestion, and excretion. Collagen [type I (70-80%) and type III (20-30%) atelocollagen] sponge grafts, freeze-dried and cross-linked, seeded with autologous MSCs, just before implantation, were used to reconstruct a 5-cm segment of dog small intestine.…”
Section: In Vitro Scaffold Assessmentmentioning
confidence: 99%
“…On the other hand, Deng et al (37) reported that Caco-2 cells cultured in a hollow ber bioreactor revealed higher expression of P-gp, which was attributed to the topographic features of the substrate. Reporting a similar result, Schweinlin et al (38) observed that the expression of P-gp and e ux of Rh-123 increased in a decellularized biological scaffold-based multicellular model of the intestinal barrier cultured in a perfusion bioreactor, comparing with the values obtained for Caco-2 monoculture from another study.…”
Section: Discussionmentioning
confidence: 99%
“…Human neural stem cell derived neurons and glia cultured in a commercially available polystyrene scaffold exhibited both high (action potential) and low-frequency (local field potential) spontaneous activity whereas no neuronal activity was detected in the 2D cultured cells 21 . Caco-2 cells demonstrated enhanced differentiation in a HFB compared to 2D culture measured by increased alkaline phosphatase, γ-glutamyltransferase and P-glycoprotein activity and higher expression of F-actin and zona occludens-1 protein 16 . Despite the advantages, the routine culturing of cells in systems other than a 2D tissue culture flask surface is still not practiced in many laboratories, although the number of publications citing 3D cell culture is growing (8-fold increase in the last 10 years.…”
Section: Introductionmentioning
confidence: 95%
“…This creates a versatile culture system with superior mass transport in which high cell densities can be reached 11 . The HFB system is well suited for the maintenance of anchorage dependent cell types and has been used to culture a variety of cells including rat pancreatic islets of Langerhans , Madin Darby canine kidney cells (MDCK) 15 and Caco-2 cells 16 to name a few.…”
Section: Introductionmentioning
confidence: 99%